Synergistic Management: Harmonizing Management of Madrasah-Pesantren within One Framework as Integrated Educational Institution - Amin Maghfuri; Sabarudin Sabarudin (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The existence of madrasas or schools based in pesantren portrays explicitly an integrated educational institution. Nevertheless, reality at the operational level does not fully indicate so. In fact madrasa and pesantren is managed partially rather than managed as an integrated education system. This article is intended to analyze the opportunities of synergizing the Islamic education system between pesantren and madrasas/schools gathered in one framework in order to become more effective islamic educational institutions. By using qualitative methode, the results of this study indicate that the opportunity to synergize pesantren and madrasas as alternative educational institutions is very wide open considering the education system that runs between the two is generally still separate. This step can be started by uniting management into an integral system, implementing an integrated and correlated curriculum and evaluating comprehensively. With the various excellences possessed by each pesantren and madrasa, synergizing these two institutions is the most effective way to realize a quality education output both in the field of religious knowledge and general knowledge.